2015
DOI: 10.3354/ame01758
|View full text |Cite
|
Sign up to set email alerts
|

River bacterioplankton community responses to a high inflow event

Abstract: Microbes drive chemical cycling and productivity within river ecosystems, but their influence may shift when intense allochthonous inputs accompany high freshwater inflow (flood) events. Investigating how floods influence microbial processes is fundamentally important for our understanding of river ecology, but is generally overlooked. We analysed bacterioplankton community composition (BCC) and abundance over 4 mo following an enormous flood event in the Hunter River, Australia, that resulted in a major fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 101 publications
6
13
0
Order By: Relevance
“…3 ). Our results are consistent with those of previous studies showing that Proteobacteria was the most abundant phylogenetic group in most river studies (Bricheux et al 2013 ; Carney et al 2015 ; Kochling et al 2017 ), and biofilms in eutrophic waters were dominated by Cyanobacteria (Danilov and Ekelund 2002 ).…”
Section: Discussionsupporting
confidence: 93%
“…3 ). Our results are consistent with those of previous studies showing that Proteobacteria was the most abundant phylogenetic group in most river studies (Bricheux et al 2013 ; Carney et al 2015 ; Kochling et al 2017 ), and biofilms in eutrophic waters were dominated by Cyanobacteria (Danilov and Ekelund 2002 ).…”
Section: Discussionsupporting
confidence: 93%
“…Genes related to hydrocarbon degradation and virulence are potentially related to industry and run-off from human waste respectively. Together with the 16S rRNA amplicon data, these results are consistent with studies in other estuarine environments that have linked the distributional dynamics of bacterial communities to nutrient gradients (Crump et al, 2004 ; Jeffries et al, 2012 ; Fortunato et al, 2013 ; Liu et al, 2015a ) and allochtonous nutrient pulses (Carney et al, 2015 ). The links between nutrient enrichment, likely derived from stormwater and sewage inputs (Birch et al, 2010 ; Hedge et al, 2014 ), and microbial biogeography within Sydney Harbor highlight the influence of anthropogenic forces on defining the microbial ecology of urban estuaries.…”
Section: Discussionsupporting
confidence: 86%
“…Both natural gradients in organic and inorganic nutrients and point source inputs of high concentrations of nutrients associated with stormwater, agricultural run-off and sewage create heterogeneity in nutrient distributions within estuaries (Paerl, 2006 ; Birch et al, 2010 ; Liu et al, 2015a ). In particular, phosphorous, and phosphates are common contaminants in urban and agricultural runoff and lead to eutrophication in aquatic systems; resulting in community shifts, reduced oxygen levels and potentially blooms of harmful organisms (Correll, 1998 ; Anderson et al, 2002 ; Paerl et al, 2003 ; González-Ortegón and Drake, 2012 ; Carney et al, 2015 ). We found that within Sydney Harbor, phosphate was a principle driver of differences among microbial assemblages and found that localized hotspots of phosphate concentration often coincided with the occurrence of microbial assemblages with differing community characteristics to those observed throughout other regions of the harbor.…”
Section: Discussionmentioning
confidence: 99%
“…Considering also that microbial communities in some of the source environments such as soil harbour a much greater diversity than aquatic communities (Crump et al, 2012), these substantial allochthonous inputs presumably accounted for the higher alphadiversity of microbial communities in the wet season (Supporting Information Table S3). Although increased river flow due to rainfall has been reported to result in more community homogeneity in the other riverine systems (Carney et al, 2015;de Oliveira and Margis, 2015), a higher spatial heterogeneity was revealed in the Ganges River in the wet season (Fig. 6A).…”
Section: Discussionmentioning
confidence: 89%